BETWEEN TWO CRISES: DO ISLAMIC BANKS SUFFER? - Rihab Grassa; Adel Sarea; Sherif El-Halaby; Anissa Naouar Damak (Journal of Islamic Monetary Economics and Finance, 2022)
This study compares the effects of the Global Financial crisis and COVID-19 pandemic on the Islamic banking sector in the Gulf Cooperation Council (GCC). Using a sample of 32 Islamic banks observed over the period 2006 to 2020, the paper reveals that the two events have different effects on the Islamic banking sector. Overall, Islamic banks are not as profitable and resilient in the COVID-19 pandemic as in the global financial crisis. However, Islamic banks in GCC countries has gained experience and become more efficient and stable over time. The policy implication of this study supports digitalization and the increased prominence of financial technology (Fintech). In addition, monetary authorities in the GCC have to introduce innovative products to help the Islamic banking sector to be more resilient to such crises.